2008
DOI: 10.2522/ptj.20070052
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Thigh Muscle Mass With Magnetic Resonance Imaging in Older Adults and People With Chronic Obstructive Pulmonary Disease

Abstract: Muscle CSA measured from a single slice provides a good indication of volume, but the most representative slice should be chosen on the basis of the muscle group of interest. Thigh circumference is not correlated with muscle volume and, therefore, should not be used as an indicator of muscle size. The development of population-specific reference equations for estimating muscle CSA from anthropometric measurements is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
74
3
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 24 publications
1
74
3
2
Order By: Relevance
“…20 Previously, some other studies have reported that upper-leg 50% girth was not correlated with knee extensor muscle strength or size, therefore these should not be used as indicators. 29,30 This discrepancy might result from the different gender group used in the previous studies compared to our study. All subjects in the present study were women, while the previous studies had included both men and women (healthy subjects or patients).…”
Section: Discussioncontrasting
confidence: 52%
“…20 Previously, some other studies have reported that upper-leg 50% girth was not correlated with knee extensor muscle strength or size, therefore these should not be used as indicators. 29,30 This discrepancy might result from the different gender group used in the previous studies compared to our study. All subjects in the present study were women, while the previous studies had included both men and women (healthy subjects or patients).…”
Section: Discussioncontrasting
confidence: 52%
“…Previously, some studies have reported that upper-leg 50% girth was not correlated with knee extensor muscle strength or size, therefore these should not be used as indicators [27,28]. This discrepancy might result from the different gender used in the previous studies compared to our study.…”
Section: Upper-leg 50% Girth Measurementcontrasting
confidence: 55%
“…Previous studies have demonstrated that there was great variability in subcutaneous fat among women compared with men [29,30]. All subjects in the present study were men, while the previous studies had included both men and women (healthy subjects or patients) [27,28]. Consequently, our results suggested that upper-leg 50% girth measurement rather than handgrip strength test was a useful method for evaluating both knee extensor muscle strength and size in healthy young men.…”
Section: Upper-leg 50% Girth Measurementmentioning
confidence: 53%
“…Although measurement of thigh circumference is simple and cheap, it may not accurately reflect local muscle mass (280). Alternatively, computed tomography (280), magnetic resonance imaging (MRI) (452), and ultrasonography (247) have been used to assess quadriceps size in COPD. Using MRI-based threedimensional shape analysis, regional shape anomalies of individual muscles were demonstrated in patients with COPD (453).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%